2007
DOI: 10.1007/s00040-007-0916-y
|View full text |Cite
|
Sign up to set email alerts
|

Population and colony structure and morphometrics in the queen dimorphic harvester ant, Pogonomyrmex pima

Abstract: The North American seed-harvester ant Pogonomyrmex (Ephebomyrmex) pima displays a dimorphism that consists of winged (alate) and wingless (intermorph) queens; both types of queens are fully reproductive. Microsatellite allele frequencies and a mitochondrial phylogeny demonstrate (1) alate and intermorph queens represent an intraspecific wing polymorphism, and (2) an absence of assortative mating and inbreeding by males. Surveys at our field site in southcentral Arizona, USA, demonstrated that only one type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Five hypotheses on the presence of unmated queens have been proposed to date: producing trophic eggs, producing male-destined eggs, working queens, failure of nuptial flight and postponement of reproduction (Vargo 1993;Bourke & Franks, 1995;Brown 1999;Kikuchi & Tsuji, 2005;Johnson et al 2007). Yamaguchi et al (2016) suggested that the two possibilities (failure of nuptial flight or postponement of reproduction) are plausible for explaining the presence of unmated queens in C. sauteri, because the unmated queens had neither egg laying nor labor.…”
Section: Discussionmentioning
confidence: 99%
“…Five hypotheses on the presence of unmated queens have been proposed to date: producing trophic eggs, producing male-destined eggs, working queens, failure of nuptial flight and postponement of reproduction (Vargo 1993;Bourke & Franks, 1995;Brown 1999;Kikuchi & Tsuji, 2005;Johnson et al 2007). Yamaguchi et al (2016) suggested that the two possibilities (failure of nuptial flight or postponement of reproduction) are plausible for explaining the presence of unmated queens in C. sauteri, because the unmated queens had neither egg laying nor labor.…”
Section: Discussionmentioning
confidence: 99%
“…The two queen morphs had similar allele distributions for four microsatellite loci; they were clustered in each population, showing that the two queen morphs could be regarded as the same species. In the harvester ant Pogonomyrmex pima Wheeler with winged and wingless queens, Johnson et al (2007) showed that these two queen phenotypes belonged to the same gene pool and the same mitochondrial clade. Some winged and wingless queens had identical mitochondrial haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of different wing sizes, the extreme condition of co-existing wingless and winged queen morphs is found in a number of species, e.g. Ephebomyrmex (now Pogonomyrmex) imberbiculus (Heinze et al 1992) and Pogonomyrmex pima (Johnson et al 2007). Female dimorphism has been found (rarely) in taxa other than social insects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although a dual reproductive strategy is not the only interpretation (see, e.g. Ribeiro et al 2006 Heinze 1999;Heinze & Keller 2000;Howard 2006;Johnson et al 2007;Howard & Jeanne 2013).…”
Section: Introductionmentioning
confidence: 99%